Role of brain-derived neurotrophic factor and nerve growth factor in the regulation of Neuropeptide W in vitro and in vivo. (15th May 2017) - Wang, Rikang; Yan, Fengxia; Liao, Rifang; Wan, Pei; Little, Peter J.; Zheng, Wenhua
Abstract: Nerve growth factor (NGF) and Brain-derived neurotrophic factor (BDNF) are neurotrophic factors involved in the growth, survival and functioning of neurons. In addition, a possible role of neurotrophins, particularly BDNF, in HPA axis hyperactivation has recently been proposed. Neuropeptide W (NPW) is an endogenous peptide ligand for the GPR7 and GPR8 and a stress mediator in the hypothalamus. It activates the HPA axis by working on hypothalamic corticotrophin-releasing hormone (CRH). No information is available about the interrelationships between neurotrophines like NGF/BDNF and NPW. We studied the effect and underlying mechanisms of NGF/BDNF on the production of NPW in PC12 cells and hypothalamus. NGF time- and concentration-dependently stimulated the expression of NPW in PC12 cells. The effect of NGF was blocked by the inhibition of PI3K/Akt signal pathway with specific inhibitors for PI3K or AktsiRNA for Akt while inhibition of ERK pathway had no effect. Moreover, BDNF concentration-dependently induced the expression of NPW mRNA and decreased the expression of NPY mRNA in primary cultured hypothalamic neurons which was also blocked by a PI3K kinase inhibitor. Finally, in vivo study showed that exogenous BDNF injected icv increased NPW production in the hypothalamus and this effect was reversed by a PI3 kinase inhibitor. These results and the fact that BDNF was able to stimulate the expression of CRH demonstrated that neurotrophines can modulate the expression of NPW in neuronal cells via the PI3K/Akt pathway and suggest that BDNF might be involved in functions of the HPA axis, at least in part by modulating the expression of NPW/NPY and CRH. Graphical abstract: Highlights: NGF stimulated the expression of Neuropeptide W (NPW) via the PI3K/Akt pathway in PC12 cells. BDNF induced the expression of NPW while decreased NPY in cultured hypothalamic neurons and in the hypothalamus of mice. BDNF can stimulate the hypothalamic expression of NPW through the PI3K/Akt pathway in mice. BDNF may stimulate the expression of CRH by modulating the expression of NPW/NPY in the hypothalamus of mice.